Creative accounting and Fraud - Huseynov, Shahmar (My University, 2010)
Günümüzde yaratıcı muhasebe muhasebe çevresinde çok bilinen konu cünki yaratıcı muhasebe uygulamalarının kullanılması son zamanlarda baş vermiş muhasebe skandallarına sebep olmuştur. Bir çok bilinen muhasebe skandalı mesela Enron, Waste Management, AOL Time Warner aynı zamanda 2008’te yaşanmış ipotek krizi yaratıcı muhasebe tekniklerinin kullanılmasından kaynaklanmaktadır. Birçok hileli finansal raporlama uygulamaları yatırımcıların yayınlanmış finansal tablolara olan güvenini sarsmıştır. Enron olayında,yönetim kurulunun skandalda büyük sorumluluğu olmuştur cünki yapılmış birçok yaratıcı muhasebe uygulamarı onların bilgisi dahilinde olmuştur. Yaratıcı Muhasebe, Hile, Hileli Finansal Raporlama

Nowadays, creative accounting is a well-known topic in accounting environment because it’s believed that almost all recently accounting scandals were the result of creative accounting practices. Many high profile accounting scandals such as Enron, Waste Management, AOL Time Warner and Mortgage Crisis which occurred in 2008, were the result of creative accounting. There have been several fraud cases which hurt investor’s confidence to the issued financial statements. Financial statement fraud together with audit failure has been hot issue recently. In the case of Enron, board of directors had the significant responsibility for the company’s collapse because Enron’s wrong accounting practices were not hidden from them. Arthur Andersen, international auditing firm, which audited Enron, can be good example of audit failure. Most of the recent emerging corporate scandals were the result of accounting problems and board oversights. Beside Enron, Xerox, AOL Time Warner, Waste Management were the most famous fraud cases which attracted attention of public recently. Key Words: Creative Accounting, Fraud, Financial Statement Fraud
Keywords: Ekonomi; Finansal Raporlama; Muhasebe; Yaratıcı Muhasebe